Space use by a male Andean bear (Tremarctos ornatus) tracked with GPS telemetry in the Macizo Chingaza, Cordillera Oriental of the Colombian Andes - Rodríguez, Daniel (2021)
For decades, telemetry has provided large amounts of ecological information for several bear species; however, for the Andean bear (Tremarctos ornatus), only three studies have available information. The use of space for this species was measured for the first time in Colombia with a male specimen tracked with GPS telemetry. Bear locations (n= 348) were obtained between October and December 2013, during the dry season. Our dry-season male home range estimates with nearest-neighbor convex-hull (K-NNCH, 24.62 km2 ) and kernel density estimate (KDE, 42.15 km2 ) slightly exceed those reported for the species in Ecuador, and our minimum convex polygon (MCP, 238.86 km2 ) quintupled estimates from Ecuador. This finding supports the hypothesis that more fragmented landscapes demand greater movements to obtain sufficient resources. K-NNCH and KDE were the most accurate methods, as they excluded degraded terrain not used by the tracked bear. Total daily traveled routes oscillated between 0.51-12.07 km. The forest-páramo ecotone, full of dry-season-fruiting Ericaceae shrubs, was the main habitat used.